ANALISIS TOTAL KEWAJIBAN MELALUI SETORAN WADIAH DAN INVESTASI BERBAGI NIRLABA DI BTPN SYARIAH UNTUK PERIODE 2016-2023 - Az-zahra, Sitti Fatimah; Vemy Suci Asih (Program Studi Manajemen Keuangan Syariah IAIN Parepare, 2025)
Banking is vital for economic growth, acting as a financial intermediary (Marshal, 2019). Islamic banks differ from conventional banks by following profit- sharing principles instead of interest. As per Law No. 10 of 1998, Islamic banks meet the needs of Muslims avoiding interest (riba) and operate alongside conventional banks, offering products like Wadiah and Mudharabah-based savings. This study analyzes the effects of Wadiah deposits and non-profit-sharing investments on total liabilities at BTPN Syariah Bank from 2016-2023. Using descriptive and quantitative methods, the results show that Wadiah deposit contribute 34.8% ,non-profit sharing investments 84.5%, and both simultaneously contribute 92.3% to total liabilities, confirming their significant impact. The research uses time series data from PT BTPN Syariah Tbk's annual reports and applies various analytical methods, including descriptive analysis and hypothesis testing, with data processed using SPSS and Microsoft Excel. The findings align with existing theories, emphasizing the crucial role that both Wadiah deposits and non-profit-sharing investments play in shaping the bank's financial liabilities. This suggests that Islamic banking products are not only compliant with Sharia principles but also significantly contribute to the bank’s overall financial stability and growth.